Legal advisers in international organizations - Wouters, Jan, 1964- (Northampton : Edward Elgar Publishing, 2023)
"This unique book presents an in-depth analysis of the provision of legal advice at international organizations. It elucidates the dual role of legal advisers as representatives of their organization and as international civil servants acting as protectors and promoters of international law. Analysing the effects of internal and external factors on the work of advisers, including organizational specificity, political influences, and institutional position, this book identifies and examines common legal practices across organizations. Chapters discuss case studies of legal advisers working at various global organizations, including the United Nations, the European Union, UNESCO, the World Health Organization and the World Bank Group, as well as regional and cross-regional organizations such as NATO and the European Space Agency. Contributors emphasise the importance of collegiality and networking between legal advisers and analyse the differences in the delivery of legal services within both governmental and private contexts. Presenting a broad perspective on the work of legal advisers at international organizations, this book will be vital reading for students, scholars, and practitioners of global governance, international law and political science. It will also be beneficial to legal advisers working for international organizations, lawyers, politicians and sociologists"--
BIBINDX
Keywords: International agencies; Lawyers; International law -- Interpretation and construction